Aspect of the biology, growth, mortality and exploitation of yellow goatfish (Upeneus sulphureus) caught by trawl in Lingayen Gulf - Galicia, Abundio M., Jr (College of Fisheries, University of the Philippines in the Visayas, 1991)
This paper presents information on the result of an 11 months study on the biology, fishery and population structure of yellow goatfish (Upeneussulphurues) caught by medium trawlers in Lingayen Gulf from June 1987 to April 1988. U. sulphureus, the most abundant and among the species under the family Mullidae, comprised 3.4% of the total catch, or an equivalent mean catch per unit effort of 1.0 kg/hr. It ranked number eight among the important species caught by medium trawlers in the area. Collected date revealed that yellow goatfish spawns during the months of March/April and December/January. This was verified by the result of recruitment analysis projected from the length frequency data. The species is most abundant in the catch during the months of June and September. The mean size at first maturity for yellow goatfish was estimated at 12.74 cm for females and 11.83 cm for males. Length-weight analysis showed that female individuals are more plump and robust than the male of the same length. Analysis of the recruitment pattern computed from length frequency data revealed two (2) pulses per year for the species. A growth increment of about 4 cm between 1 to 2 years of age and 1.42 cm between 2 to 3 years of age were calculated for the species having a growth coefficient K=0.9736/yr and loo=16.09 cm. This implies that it will take approximately 2.8 years for the species to grow to a length of 15.0 cm. Most of the yellow goatfish caught by the medium trawlers are between 8 months to 2 years of age with a size range of 8 to 14 cm. The length at first capture was estimated at 9.63 cm and the species become fully exploited at length 10.6 cm (both sexes). The stomach content analysis revealed that shrimp is the major food item in their diet.